The effects of plyometric jump training on jump and sportspecific performances in prepubertal female swimmers - Sammoud, S.; Negra, Y.; Bouguezzi, R.; Moran, J.; Granacher, U.; Chaabene, H. (Journal of Exercise Science & Fitness, 2021)
Dry land-training (e.g., plyometric jump training) can be a useful mean to improve swimming performance. This study examined the effects of an 8-week plyometric jump training (PJT) program on jump and sport-specific performances in prepubertal female swimmers. Methods